Zircon U–Pb geochronology, Hf isotopic compositions, and petrogenetic study of Abor volcanic rocks of Eastern Himalayan Syntaxis, Northeast India: Implications for eruption during breakup of Eastern Gondwana. (6th March 2019) - Singh, Athokpam Krishnakanta; Chung, Sun‐Lin; Bikramaditya, Rajkumar; Lee, Hao‐Yang; Khogenkumar, Shoraisam
Abstract : This paper reports new zircon U–Pb ages and Hf isotopic compositions of felsic units of the Abor volcanic rocks (AVR) of Eastern Himalayan Syntaxis (EHS), Northeast India, and discusses their relationship to the Kerguelen plume activity. The AVR are bimodal and predominantly constituted by mafic rocks with minor felsic units. Mafic volcanics are identified as basalt and basaltic andesite with light rare earth elements (LREE) enriched and slightly depleted heavy rare earth elements (HREE) pattern without Eu anomalies. Low concentrations of LILE, high contents of Fe2 O3, and other incompatible trace elements ratios reflect enriched nature of these mafic volcanics. Felsic volcanic rocks are dacitic to rhyolitic in composition, which have high REE content, high LREE/HREE, and pronounced negative Eu anomalies. Enriched LREE, high Th/Nb, Ce/Nb ratios, and variations in Rb/Zr, K/Rb, La/Sm ratios with negative anomalies of Ba, Nb, Sr, P, Ti in felsic rocks suggest substantial contribution of crustal contamination at the time of eruption. Zircons from felsic units yield an average U–Pb age of ~132 Ma and unradiogenic (ƐHf (t) < 0) Hf isotope values of −7.0 to −13.3 with model ages between 1.5 and 2.1 Ga, suggesting old crustal assimilation in their genesis. The AVR were emplaced in the continental rift tectonic setting, and depth of the magma source is confirmed as near spinel stability zone. The AVR are positively comparable with other flood basalts that were formed due to the Kerguelen plume activity. Therefore, our combined new geochemical and geochronological data show that the AVR were emplaced at early stage (~132 Ma) of eastern Gondwana breakup due to outbreak of the Kerguelen plume. This study thus supports the idea of the Kerguelen plume affecting a large area of Eastern India, Western Australia, and Antarctica during early stage of Gondwana breakup.